PENGARUH RASIO KEUANGAN, UKURAN PERUSAHAAN, ARUS KAS AKTIVITAS OPERASI PADA RETURN SAHAM - Pratiwi, Trisna Windika; Putra, I Wayan (E-Jurnal Akuntansi, 2015)
The purpose of this study was to determine the effect of financial ratios, the size of the company, and cash flow operating activities on stock returns in Indonesia Stock Exchange 2011-2013. The independent variable in this study is liquidity, profitability, leverage, activity, firm size and cash flow operating activities. The sample in this study amounted to 35 companies with nonprobability sampling method. Data was collected by non-participant observation techniques. Data analysis techniques used in this research is multiple linear regression analysis. The results showed that the variables of liquidity, profitability, and firm size has positive effect on stock returns, the variable leverage negative effect on stock returns, while the activity and cash flow operating activities have no effect on stock returns
Keywords: financial ratios, firm size, cash flow operating activities, stock return